Somatic comorbidity and the progression of cognitive impairment - Bidzan, Leszek; Jurek, Paweł; Olech, Michał; Bidzan-Wiącek, Monika; Bidzan-Bluma, Ilona; Bidzan, Mariola (Frontiers in Aging Neuroscience, 2023)
Background There are usually multiple factors underlying dementia in old age. Somatic comorbidity is one important element that influences the progression of cognitive impairment. Objective The goal of this study was to assess the relationship between the progression of cognitive impairment and the presence and severity of comorbidities based on a four-year observation. Material Out of 128 patients from the Clinic for Outpatients in Gdansk, who were recruited into the study based on the criteria of the Working Group on Mild Cognitive Impairment, a total of 93 participants completed the four-year observation. Only the data from participants who completed the full period of observations were analysed. The mean age of the group was M = 75.93 (SD = 9.43). The level of progression of cognitive impairment was measured using the Clinical Dementia Rating Scale – Sum of Boxes, the severity of comorbidities was measured using the modified Cumulative Illness Rating Scale, and, additionally, at the time of inclusion in the study, participants were assessed using the MMSE scale and the Activity Scale, and sociodemographic data were collected. The Generalized Estimating Equations method was employed to fit a marginal model for analyzing the data collected in a repeated measures design. The tested model elucidated the role of the overall severity of comorbidities in explaining the progression of cognitive impairment, while controlling for everyday activity and basic demographic variables. Results During the four-year observation, a significant decline in cognitive function (B = 1.86, p < 0.01) was observed in the examined sample. The statistical analysis revealed that individuals with higher overall severity of comorbidities exhibited significantly more pronounced progression of cognitive impairment over time. Regarding particular comorbidities, metabolic diseases were found to be associated with a poorer prognosis (rho = 0.41, p < 0.05). Furthermore, a time physical activity interaction was identified as predicting cognitive impairment, indicating that individuals who were more physically active at the beginning of the study exhibited significantly less pronounced progression of cognitive impairment over the course of the 4 years. Conclusion This study suggests the important roles of comorbidities and physical activity for the prognosis of mild cognitive impairment.